Implementation of Innovative Bridge Technologies : Technical Guidance Note - World Bank (Washington, DC, 2022)
Bridges are critical components in the transport network and serve as vital links significantly contributing to social connection and economic production across the Pacific. Bridges are intrinsically exposed to natural hazards and impacted by climate change. Delays associated with the ongoing maintenance of bridges can also put additional strain on this infrastructure and leave them more susceptible to damage. Collectively, these issues serve as a catalyst to the continuing efforts of donors to support the research, exploration, development, and implementation of bridge solutions that consider a local context. This technical guidance note highlights the methodology and lessons learned from the implementation of innovative bridge technologies assessment study and its application under the World Bank-funded Solomon Islands Roads and Aviation Project. This case study focused on the use of a selected range of modular bridges that provide a low maintenance, long-term, whole of life bridge solution which illustrates how the quality of infrastructure investment can be improved by improving economic efficiency and building resilience. It also outlines a way forward for the implementation of these bridge technologies across the Pacific region.